The politics of co-design in ICT for sustainable development. Issue 1 (2nd January 2020) - Kendall, Linus; Dearden, Andy
ABSTRACT: In this paper, we discuss an approach to co-design in ICT for sustainable development. We first set out to consider sustainable development as incorporate a concern for resilience, adaptability, and autonomy. We then draw on an ongoing participatory design project to illustrate how co-design projects can be configured, along with the political choices that this entails, to support such development.